Pajak Tanah Sebagai Instrumen Pendapatan Keuangan Publik Dalam Ekonomi Islam - Ahmad Syakur (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2015)
Tax is the main source of state revenue in this modern era, but one of the big problems is that tax in mostÂ moslemsâ€™ opinion is not a part of religious obligation. Meanwhile, taxation concept in Islam was known andÂ implemented in the early Islamic rule. Many classic ulama studied about al-kharaj and taxation systems, andÂ one of them was Ibn Rajab al-Hambali (Died in 795 A.H or 1393 A.D), but these books did not have take moreÂ moslemsâ€™ attention.Â This is a library reseach and usea qualitative method with models of discriptive, analytic and eksplanatory. TheÂ primary source of data is the book written by Ibn Rajab al-Hambali, al-IstikhrÄj Li Aá¸¥kÄm al-kharÄj. SeconderyÂ sources of data are all of books and articles that talk about the topic. Descriptive and comparative methods wereÂ then used to analyze the data.Â The results of this reseach are: 1) The concept of Al-kharaj or land tax in kitab al-IstikhrÄj Li Aá¸¥kÄm al-kharÄjÂ is based on ijtihad of imam for being beneficial in the present time and in the next time. So, the implementationÂ of al-kharaj throughout the Islamic history is dynamic and flexibel. The dynamism and flexibility in the policyÂ of al-kharÄj include the dynamism of its policy changes and the rationale behind the reduction in tax rates,Â the policy of affordable taxes, the changes in types of taxes and the collection policy; 2) Taxation system in theÂ Islamic public finance that is studied in kitab al IstikhrÄj Li Aá¸¥kÄm al-kharÄj is matching and suitable withÂ principles of tax in public finance proposed by Adam Smith that is known as four maxims of taxation: equity,Â certainty, convenience and economy. The dynamism in the implementation of al-kharÄj enable us to developÂ the Islamic taxation systems, that is synchronous with management of zakat, so that the justice for all citizens,Â moslem and not moslem, can be realized.